2018
DOI: 10.1182/bloodadvances.2018021931
|View full text |Cite
|
Sign up to set email alerts
|

Blood manufacturing methods affect red blood cell product characteristics and immunomodulatory activity

Abstract: Transfusion of red cell concentrates (RCCs) is associated with increased risk of adverse outcomes that may be affected by different blood manufacturing methods and the presence of extracellular vesicles (EVs). We investigated the effect of different manufacturing methods on hemolysis, residual cells, cell-derived EVs, and immunomodulatory effects on monocyte activity. Thirty-two RCC units produced using whole blood filtration (WBF), red cell filtration (RCF), apheresis-derived (AD), and whole blood-derived (WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 62 publications
4
43
0
Order By: Relevance
“…Monocytes were treated with 1 ml of day 7, day 21 or day 42 RCC supernatants (20% v/v in culture media) followed by 4‐h incubation (37°C, 5% CO 2 ). The 20% v/v of RCC supernatants chosen was an approximate volume ratio of a 20 ml/kg RCC transfusion . To evaluate the phagocytic function of the pooled cryopreserved BC‐derived monocytes, monocyte monolayers were incubated for 2 h with 1 ml of 5% anti‐D‐sensitized group O Rh‐positive RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…Monocytes were treated with 1 ml of day 7, day 21 or day 42 RCC supernatants (20% v/v in culture media) followed by 4‐h incubation (37°C, 5% CO 2 ). The 20% v/v of RCC supernatants chosen was an approximate volume ratio of a 20 ml/kg RCC transfusion . To evaluate the phagocytic function of the pooled cryopreserved BC‐derived monocytes, monocyte monolayers were incubated for 2 h with 1 ml of 5% anti‐D‐sensitized group O Rh‐positive RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…Jordan et al found similar results and showed that RBC from female donors had lower haemolysis than those from male donors [23]. It has also been shown that extracellular vesicle (EV) release varies by RBC manufacturing method, that EV release levels are lower in RBC produced by the RBC filtration method [24], and that there are subsequent differences in these products' immunomodulatory effects [25]. Differences in levels of residual plasma among RBC manufacturing methods have also been found, with WB filtration methods having significantly higher levels than RBC filtration methods [7].…”
Section: Discussionmentioning
confidence: 90%
“…Both PLT‐ and WBC‐derived EVs have been shown induce endothelial cell activation, inflammatory cytokine release, and enhanced expression of WBC adhesion factors . However, PLT‐derived EVs have also been shown to promote release of anti‐inflammatory TGF‐β from monocytes, and immune‐suppressive effects of RBC products on monocytes across component preparation methods correlate with PLT‐derived EV quantities . Given these differences, it is not surprising that documented immunomodulatory effects of transfused EVs are highly varied.…”
Section: Evidence For Immunomodulatory Effects Of Evs In Blood Productsmentioning
confidence: 99%